Firm's perception of economic policy uncertainty and corporate innovation efficiency - Han Zhou; Xiang Zhang; Rui Ruan (Journal of Innovation & Knowledge (JIK), 2023)
Current Economic Policy Uncertainty (EPU) indicators are highly correlated with macroeconomic growth. To better reveal the EPU perceived by each firm, a firm-level EPU index is constructed using a text mining method. Using data of Chinese A-share listed companies from 2011 to 2020, this study examines the impact of a firm's perception of EPU on corporate innovation efficiency, computed using Stochastic Frontier Analysis (SFA) with a time-varying decay model. The empirical results show that corporate innovation efficiency decreases with a firm's perception of EPU. Additionally, the impact of traditional EPU indicators on innovation efficiency becomes statistically insignificant after the macroeconomic variable is added, demonstrating the importance of introducing firm-specific perceptions of EPU. Moreover, this negative impact is attenuated for firms with higher board independence and lower board ownership, while State-Owned Enterprises (SOEs) are less impacted. Furthermore, the impact of a firm's perception of EPU on corporate innovation efficiency is more pronounced for high-tech firms and those without political connections. We propose the following policy implications: First, it is vital for governments to provide stable economic circumstances to maintain corporate innovation efficiency. Second, mixed ownership reform is crucial in China; the risk-taking of non-state-owned firms will be greatly improved; thus, the innovation efficiency of non-state-owned firms will improve.
Keywords: G18; G34; O32; 650; Corporate innovation efficiency; Economic policy uncertainty; Firm's perception